Mechanical characterization and constitutive parameter identification of anisotropic tubular materials for hydroforming applications - Khalfallah, Ali (2015)
This paper aims to identify the constitutive parameters of anisotropic tubular materials and to verify the accuracy of models' prediction. The identification of the constitutive parameters is based on information obtained from tensile tests, performed on samples cut from the tubes, and from the free tubular bulge test, using a home-developed bulge forming machine. Two tubular materials exhibiting different anisotropic behaviour and work hardening characteristics are investigated: a mild steel S235 seamed tube and an aluminium alloy AA6063 extruded tube. It is shown that advanced phenomenological yield functions, including a large number of anisotropy parameters, can accurately describe the plastic flow of highly anisotropic tubular materials during the tube hydroforming process. However, parameter identification procedure of advanced yield criteria requires a high number of experimental tests. Thus, in order to enable the parameter identification of these yield criteria when using a reduced set of experimental results, the present study develops a method that combines tensile tests with (i) a free bulge test, which is used to characterize the biaxial stress state experienced by the tube during the bulge testing, and (ii) some generated artificial input data. Finally, the proposed method shows an excellent agreement between numerical predictions and experimental results.